ヒガシ ナンキョク タイリク ENDERBY LAND ノ SANDERCOCK NUNATAK グン ノ チシツ ニ ツイテ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 白石, 和行; シライシ, カズユキ; 渡辺, 興亜; ワタナベ, オキツグ; 木崎, 甲子郎; キザキ, コウシロウ; SHIRAISHI, Kazuyuki; WATANABE, Okitsugu; KIZAKI, Koshiro (国立極地研究所, 1972)
P(論文) The Sandercock. Nunataks (68°33'S, 52°07'E) are composed of several small nunataks which are tentatively named A, B, C and D. Nunatak "A" consists mainly of hornblende-biotite gneiss and Nunatak "B" of hypersthene-garnet gneiss and garnet gneiss. Nunatak "C" is composed of hypersthene-hornblende gneiss. They are associated with aplites, pegmatites and metabasites. The petrographic observations under the microscope reveal that the unstable hypersthene signifies the transition of the granulite facies conditions to the amphibolite facies conditions. The transition is not unusual throughout the East Antarctic platform, particularly in the Lutzow-Holm Bukt area and Queen Maud Land. departmental bulletin paper